Language Style in Digital Communication Interactions at Advertising Agencies - Huwaidah, Fatimah; Heriyati, Nungki (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study aims to analyze linguistic phenomena in digital communication conducted by advertising agencies, particularly in their interactions with influencers as strategic partners. The research focuses on hybrid language styles, code-switching practices, and personalization strategies in shaping communication that is both effective and professional, yet friendly. A qualitative descriptive method was employed, with data collected through in-depth interviews involving 13 influencers and 3 agency representatives (Maleo, VML, and Kanan Kiri). The data were analyzed using thematic analysis to identify linguistic patterns and the pragmatic functions of commonly used phrases in digital interactions. The findings reveal that the language style adopted by advertising agencies reflects an adaptation to the digital communication landscape, where phrases like